A strategy for L-isoleucine dioxygenase screening and 4-hydroxyisoleucine production by resting cells. Issue 1 (1st January 2018) - Zhang, Chenglin; Ma, Jie; Li, Zhixiang; Liang, Yunlong; Xu, Qingyang; Xie, Xixian; Chen, Ning
ABSTRACT: L -Isoleucine dioxygenase (IDO) specifically converts L -isoleucine(L -Ile) to 4-hydroxyisoleucine(4-HIL). To obtain IDO with improved activity, a strategy was developed that is dependent on the restoration of succinate-minus E. coli cell growth by the coupling of L -Ile hydroxylation and the oxidation of α-ketoglutarate(α-KGA) to succinate. Five mutants were obtained with this strategy, and the characteristics of IDO M3, which exhibited the highest activity, were studied. The catalytic efficiency, thermal stability and catalytic rate of IDO M3 were significantly improved compared with those of wild-type IDO. Moreover, an efficient method for the biotransformation of 4-HIL by resting cells expressing IDO M3 was developed, with which 151.9 mmol of 4-HIL/L (22.4 g/L) was synthesized in 12 h while the substrates seldom exhibited additional consumption.